MAGNET: An optimized DevOps framework for efficient software integration and orchestration in the IoT-Edge-Cloud Continuum - Agorogiannis, Evangelos; Petrakis, Kostas; Antonopoulos, Grigorios; Anagnostopoulos, Themistoklis; Grigoropoulos, Nasos; Benomar, Zakaria (2025 6th International Conference in Electronic Engineering & Information Technology (EEITE), 2025)
This paper introduces MAGNET, a DevOps framework comprising Continuous Integration/Continuous Deployment practices, alongside flexible development and integration infrastructures, as applied in COGNIFOG, an innovative computing ecosystem currently under development that uses decentralized decision making, machine learning, and distributed computing to enhance autonomy, adaptability, and scalability within the IoT-edge-cloud continuum. The proposed approach ensures efficient, reliable, and seamless framework integration, offering key insights into integration architecture, data flow management, and the adoption of advanced technologies. This work demonstrates the efficiency and adaptability of the COGNIFOG ecosystem through three real-world trials in smart cities, e-health, and smart manufacturing, along with the creation of a comprehensive QuickStart Guide for deployment, offering a robust solution for the complexities of next-generation computing environments.